THE RELATION BETWEEN DIET, ATTITUDE AND LEVEL OF KNOWLEDGE OF THE ELDERLY WITH LEVELS OF URIC ACID IN THE BLOOD AT SUKARAYA HEALTH CENTER WORK AREA - Berta Afriani; Toto Harto; Sari, Debi Oktarani (Majalah Kedokteran Sriwijaya, 2025)
The condition that can cause swelling, burning, and unbearable pain in the joints is called gout. Diet is an effort to regulate the amount and type of food with health information about nutritional status, prevention and cure of disease. In general, the purpose of the study is to determine the relationship between diet, attitudes and knowledge levels of the elderly with Levels of uric acid in the blood at Sukaraya Health Center Work area in 2024. This study used a quantitative correlational method with a cross-sectional approach, a total of 50 samples. The results of the study were obtained from questionnaires and observation sheets, the research will be written in a frequency distribution table and the results will be analyzed. Within this research obtained using the test of chi-square, namely there is a significant Relationship among diet and Levels of uric acid (p value = 0.000), there is a significant Relationship among attitudes and Levels of uric acid (p value = 0.004), and there is a significant Relationship among the level of knowledge and Levels of uric acid (p value = 0.000) at Sukaraya Health Center Work area. The research's results suggest that is a correlation with the elderly's blood uric acid levels at Sukaraya Health Center Work Area and their nutrition, attitudes, and knowledge levels.